2020
DOI: 10.1002/dvdy.151
|View full text |Cite
|
Sign up to set email alerts
|

Role of noncanonical Wnt ligands and Ror‐family receptor tyrosine kinases in the development, regeneration, and diseases of the musculoskeletal system

Abstract: The Ror-family receptor tyrosine kinases (RTKs), consisting of Ror1 and Ror2, play crucial roles in morphogenesis and formation of various tissues/organs, including the bones and skeletal muscles, the so-called musculoskeletal system, during embryonic development, by acting as receptors or coreceptors for a noncanonical Wnt protein Wnt5a. Furthermore, several lines of evidence have indicated that Ror1 and/or Ror2 play critical roles in the regeneration and maintenance of the musculoskeletal system in adults. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 104 publications
(192 reference statements)
0
24
0
Order By: Relevance
“…In vertebrates, ROR2 and ROR1 bind to non-classical Wnt5a protein through their CRD and act as receptors or co-receptors for Wnt5a to activate non-classical Wnt pathways (β-cateninindependent pathways), including planar cellular polarization pathways and Wnt-Ca 2+ pathways (Oishi et al, 2003;Yamamoto et al, 2007;Gao et al, 2011;Kamizaki et al, 2020). Recently, studies showed that the Wnt5a-ROR2 pathway was not only involved in the development of cartilage but also associated with the function of osteoblasts and osteoclasts (Chen et al, 2019;Uehara et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vertebrates, ROR2 and ROR1 bind to non-classical Wnt5a protein through their CRD and act as receptors or co-receptors for Wnt5a to activate non-classical Wnt pathways (β-cateninindependent pathways), including planar cellular polarization pathways and Wnt-Ca 2+ pathways (Oishi et al, 2003;Yamamoto et al, 2007;Gao et al, 2011;Kamizaki et al, 2020). Recently, studies showed that the Wnt5a-ROR2 pathway was not only involved in the development of cartilage but also associated with the function of osteoblasts and osteoclasts (Chen et al, 2019;Uehara et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As a member of ROR family receptor tyrosine kinase, receptor tyrosine kinase like orphan receptor 2 (ROR2) is a 943-amino acid transmembrane protein tyrosine kinase encoded by the ROR2 gene (van Bokhoven et al, 2000). The extracellular domains of ROR2 mainly include an immunoglobulin-like functional domain, a cysteine enrichment domain (CRD), and a kringle domain, while the intracellular domains include a tyrosine kinase domain (TKD), a proline-rich domain, two serine/threonine-rich domains, and a short C-terminal tail (Endo and Minami, 2018;Kamizaki et al, 2020). ROR2 is widely expressed in a variety of tissues, including the heart, brain, and lung and is also involved in the development of the nervous system and the skeletal system (Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The ROR subfamily members were designated as "orphan" receptors because their ligands have not been identified for many years. Now it is known that ROR family members are receptors for Wnt family signaling molecules Wnt5a/b and Wnt16, with Wnt5a as the primary ligand (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt signaling pathway is widely distributed in invertebrates and vertebrates and is a highly evolutionarily conserved signaling pathway. Wnt signaling plays a crucial role in physiological processes, such as the early development of animal embryos [ 30 ], organ formation [ 31 ], and tissue regeneration [ 32 ]. Binding of the Wnt molecule to a transmembrane receptor triggers the accumulation of β -catenin in the cytoplasm and its subsequent translocation into the nucleus via interaction of the receptor with Dishevelled (DVL) and a series of cytoplasmic proteins [ 33 ].…”
Section: Introductionmentioning
confidence: 99%